Marketing of Educational Services - Sofrić, Ajda; Zidar, Petra; Vukovič, Goran (Celovita pot izobraževanja: Od ideje do mreženja, 2026)
This chapter examines marketing for educational institutions which has its specificities in the service sector. Rapidly changing conditions and fierce competition require a different kind of approach, as educational institutions have used until now. Digital technology plays a key role so that new ways of advertising services and reaching new customers are possible for educational institutionsThe analysis focuses on the factors that have an impact on the decision for educational service, ways of acquiring knowledge, challenges in transferring knowledge to the work environment, the success of training participants in taking the final knowledge assessment and the use of digital technology in the educational process. Findings revel that the quality of educational service is still one of the most important factors while choosing the educational service. Digital technology has a great impact on acquiring knowledge, especially acquiring knowledge online and for that reason acquiring knowledge is also faster and easier. Access to relevant literature and e-materials also significantly contribute to the success of training participants in completing the final knowledge assessment. Based on these insights, proposals for improvement include adjustments of acquiring knowledge and the use of digital technology in the educational process.